Effect of chlorophyll in alginate-based edible film in inhibiting spoilage of fish snacks - Eko Nurcahya Dewi; Asmi Citra Malina A.R. Tassakka; Mochammad Yuwono; Eko Agus Suyono; Lukita Purnamayati; Jamaluddin Fitrah Alam (Hasanuddin University Food Science and Technology Study Program, 2022)
Edible films are environmentally biodegradable materials used for food packaging. The edible green alga Caulerpa racemosa has antimicrobial properties; however, its chlorophyll-based bioactive compounds can be damaged when heated so it is prepared in microcapsules. Our research evaluated the effect of Caulerpa microcapsules on an alginate-based edible film on film properties and food spoilage. The microcapsules were used at concentrations of 0%, 0.5%, 1%, and 1.5%. The edible film was measured for film properties, total phenolic content (TPC), antioxidant activity (DPPH), functional group (FTIR) and microstructure (SEM). Food spoilage was evaluated on a popular fish-based product (fish bubble snacks). Bacterial strains of Escherichia coli and Staphylococcus aureus were used to evaluate antimicrobial effectiveness of the edible films. The addition of Caulerpa microcapsules had no significant negative effect on physical properties of the alginate-based film, while the smoother and more homogenous surface should enhance the barrier properties of the film. The slow and evenly distributed release of active compounds from the microcapsules increased resistance to Rhizopus sp. and significantly reduced the proliferation of E. coli but not S. aureus on coated fish snacks. Caulerpa racemosa can be used to enhance the effectiveness of alginate-based films in delaying spoilage and could extend product shelf-life